Pengaruh Customer Based Brand Equity(CBBE) Merek Snack terhadap Keputusan Pembelian Konsumen Pelajar Di Kabupaten Grobogan Jawa Tengah - Sentot Suciarto A.; Markus Widyanto; Rustina Untari (JEMAP, 2018)
The marketing of corn competitive product in Grobogan Regency was developed by increasing its value added by making corn snack. This research was done in Grobogan Regency toward 180 students comprising Elementary School, Yunior and Senior High School, each 60 respondents consuming corn snack. Using regression analysis, it was known that there is significant influence from variables constructing Customer Based Brand Equity (CBBE) by Keller. Variables which influence positive and significant were Brand Imagery, Brand Performance and Brand Resonance. It was found that R equals 0.551 and adjusted R square or determinant coefficient was 0.279 or influence of CBBE toward BuyingDecision was 27.9 percent.